Oral tradition in the study of ulayat land disputes in West Sumatra - Dewi, Susi Fitria (UI Scholars Hub, 2010)
Land is a society's potent symbol of wealth, social power, and culture. A long time ago, when extensive jungles and forests still abounded, there were probably no serious conflicts over land ownership. Groups were free to roam about and to open up land to extend their farming area in accordance to their needs. Groups in society marked the land they had cultivated to proclaim their ownership. These marks could be very simple and could simply be a tree, a big stone, or a piece of iron hammered into the soil, or they used the physical condition of the land itself such as rivers, lakes, hills etcetera as borders to distinguish their land from that of others. Minangkabau traditional society never recorded these borders in writing on paper, leaves, or stones or any other means as many peoples in other parts of the world do. Rather, they deemed it sufficient to use natural symbols to demarcate the important agreements they had made between them orally.